A heat history programmable structural color patterned security label and method of making the same
Patent Information
- Application Number
- CN202611166664.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0003]然而,现有胆甾相液晶结构色图案化技术仍存在以下不足:其一,基于结构色油墨印刷或涂布的图案化技术,图案一经制成即恒定可见,不具备常态隐藏功能,防伪信息易被直接观察和仿制;其二,基于光响应手性剂(如偶氮苯类手性开关)的光写入图案化技术依赖特定波长光源和昂贵的光响应分子,图案在环境光照下易被擦除或篡改,稳定性不足;其三,基于温致变色胆甾相液晶的技术仅能反映当前温度,温度恢复后颜色随之可逆复原,不能记录样品曾经经历的热历史,更无法实现先经历预设热历史、后显现图案的延迟显现功能
本发明可在普通实验室条件下实现结构色图案化,并可规模化商业应用,其图案可设计为二维码、条形码、文字或图形;图案显现依赖预设热历史过程,具有较好的隐蔽性和识别性;制备条件温和,原料来源方便,适用于防伪标识、信息加密和温度历史记录等场景。
Smart Images

Figure CN122676730B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of liquid crystal functional materials and information encryption technology, specifically to an anti-counterfeiting label with thermal history programmable structural color patterning and its preparation method. Background Technology
[0002] Cholesteric liquid crystals possess a periodic helical structure, enabling them to selectively reflect light of specific wavelengths and exhibit structural colors. This makes them valuable in display, anti-counterfeiting, sensing, and decorative materials. In the field of anti-counterfeiting, traditional printing inks, fluorescent inks, and laser holography, among other basic anti-counterfeiting methods, convey static information. Their anti-counterfeiting features can be directly observed, easily scanned, photographed, and mass-produced, resulting in limited anti-counterfeiting strength. Structural color anti-counterfeiting, relying on physical periodic structures to generate color, is difficult to replicate using ordinary pigments and printing processes, representing a significant development direction in anti-counterfeiting technology in recent years.
[0003] However, existing cholesteric liquid crystal structural color patterning technologies still have the following shortcomings: First, patterning technologies based on structural color ink printing or coating are always visible once the pattern is made, lacking a normal hiding function, and anti-counterfeiting information is easily observed and counterfeited. Second, photowriting patterning technologies based on photoresponsive chiral agents (such as azobenzene chiral switches) rely on specific wavelength light sources and expensive photoresponsive molecules, and the pattern is easily erased or tampered with under ambient light, resulting in insufficient stability. Third, technologies based on thermochromic cholesteric liquid crystals can only reflect the current temperature, and the color reversibly recovers after the temperature returns to normal. They cannot record the thermal history that the sample has experienced, let alone achieve the delayed display function of experiencing a preset thermal history before the pattern appears. In other words, existing technologies have difficulty simultaneously achieving normal pattern hiding, thermal history recording and triggered display, and the repeatable appearance and disappearance of the pattern.
[0004] In liquid crystal alignment technology, polyvinyl alcohol (PVA) triboelectric alignment is a mature, low-cost, and film-forming process, making it a commonly used alignment material in cholesteric liquid crystal devices. However, conventional PVA alignment layers have a simple chemical composition and uniform surface properties across the entire film, making regional programming impossible and thus lacking patterning capabilities. Existing patternable alignment schemes mostly rely on azobenzene-based photo-controlled alignment materials, requiring polarized ultraviolet exposure equipment, which is complex, costly, and carries the risk of relaxation failure under long-term illumination. On the other hand, PVA side chains are rich in hydroxyl groups, which can form boronic acid ester bonds, acetal bonds, or carbonate bonds with small molecules containing borate, aldehyde, or activated carbonyl groups, respectively. These chemical bonds exhibit controllable sensitivity to water, acids, or alkalis. This provides the possibility of regionally modifying PVA alignment layers through chemical means, but there are no reports in the current technology of using the selective breaking of such chemical bonds to write hidden patterns in the alignment layer and combining this with the thermal history of cholesteric liquid crystals to achieve delayed pattern display.
[0005] Therefore, in view of the shortcomings of the above-mentioned existing technologies, there is a need to provide a structural color patterning method and anti-counterfeiting label that does not require light-controlled orientation equipment, has mild preparation conditions, keeps the pattern hidden in normal conditions, can be triggered by preset thermal history and can be repeatedly revealed and hidden. Summary of the Invention
[0006] The purpose of this invention is to provide a thermal history-programmable structural color patterned anti-counterfeiting label and its preparation method. The preparation method belongs to the thermal history-programmable structural color patterning method based on cholesteric liquid crystal. This method, through the combination of a functionalized alignment layer, local patterning processing, and cholesteric liquid crystal, makes the resulting label have a hidden pattern or low contrast under normal observation conditions. After undergoing a preset thermal history process, the structural color pattern appears, making it clearly visible and recognizable by barcode scanning devices. Specifically, when the label has not undergone the thermal history process beyond the clearing point, both the processed and unprocessed areas exhibit structural color during the heating and cooling process, with a consistent appearance and a hidden pattern. When the label is heated past the clearing point and cooled to the cholesteric phase temperature range, the unprocessed area exhibits no structural color while the processed area retains its structural color; the contrast between the two makes the pattern visible.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a thermal history programmable structural color patterned anti-counterfeiting label, comprising the following steps: S1. Prepare an orientation layer coating solution containing polyvinyl alcohol and functionalized small molecules, coat it onto a transparent substrate to form a film, and dry or anneal it to obtain a substrate with an orientation layer. The functionalized small molecule is selected from one of the structures shown in formula (Ⅰ), (Ⅱ), and (Ⅲ): , , ;
[0008] Wherein, R is a liquid crystal compatibility end composed of at least one of C1-C20 alkyl, C1-C20 alkoxy, phenyl, naphthyl, biphenyl, cyanophenyl, and cyanobiphenyl. S2. The alignment layer is surface-oriented using a friction method or equivalent friction method; then, a local patterning process is performed on the surface after the alignment process to form a hidden pattern area containing a preset pattern on the alignment layer. The chemical properties of the patterning process and the functionalized small molecules satisfy the following relationship: When the functionalized small molecule is selected from the structure of formula (I), the processing medium used for patterning is selected from at least one of water, water vapor, acidic solution or acidic atmosphere; When the functionalized small molecule is selected from the structure of formula (II), the processing medium used for patterning is selected from at least one of acidic solution or acidic atmosphere; When the functionalized small molecule is selected from the structure of formula (III), the processing medium used for patterning is selected from at least one of alkaline solution or alkaline atmosphere; S3. Take two patterned substrates with alignment layers and assemble them into a liquid crystal cell with their orientation directions parallel and opposite, and place the alignment layer inside the liquid crystal cell. S4. Cholesteric liquid crystal, including nematic liquid crystal and chiral agent, is poured into a liquid crystal cell and cured to obtain an anti-counterfeiting label based on the thermal history programmable structural color pattern of cholesteric liquid crystal.
[0009] In this invention, the functionalized small molecule includes a reactive end and a liquid crystal compatible end. For example... Figure 1 As shown, during the grafting reaction, the reaction end undergoes borate esterification, acetalization, or carbonate esterification with the hydroxyl groups of polyvinyl alcohol, resulting in dehydration and bond formation, thereby covalently grafting the liquid crystal compatibility end R to the PVA molecular chain. During the hydrolysis reaction, under water, acid, or alkaline conditions matching the bond type, the corresponding borate ester bond, acetal bond, or carbonate bond breaks, removing the side chain R group and restoring the original hydroxyl group of PVA. The liquid crystal compatibility end is composed of at least one of C1-C20 alkyl, C1-C20 alkoxy, phenyl, naphthyl, biphenyl, cyanophenyl, or cyanobiphenyl. The role of the liquid crystal compatible terminal in the patterning process is to enable the area grafted with the liquid crystal compatible terminal (i.e., the unpatterned area) to exhibit a structureless color state during its thermal history of heating past the clearing point and then cooling to the cholesteric phase temperature region. This creates a contrast between the structureless color and the patterned area (the area where the liquid crystal compatible terminal has been locally removed), thus revealing the hidden pattern. If the liquid crystal compatible terminal is missing or does not meet the requirements, the aforementioned structureless color background cannot be formed in the unpatterned area, and the pattern cannot be revealed.
[0010] In this invention, the orientation layer coating solution also contains a catalyst or auxiliary agent adapted to the grafting reaction of the functionalized small molecules. Specifically, when the functionalized small molecule is selected from the structure of formula (II), the orientation layer coating solution also contains an acid catalyst (such as p-toluenesulfonic acid); when the functionalized small molecule is selected from the structure of formula (III), the orientation layer coating solution also contains an acid-binding agent and / or an acylation catalyst (such as at least one of triethylamine and 4-dimethylaminopyridine).
[0011] For example, the preferred chemical structural formula of the functionalized small molecule of the present invention is as follows: ; 4-(octyloxy)phenylboronic acid; ; 4-(hexyloxy)phenylboronic acid; ; 4'-Cyanobenzyl-4-boronic acid; ; 4-(octyloxy)benzaldehyde; ; 4-(hexyloxy)benzaldehyde; ; 4'-Formylbiphenyl-4-nitrile; ; 6-(4'-cyanobiphenyloxy)hexane-1-ol; ; 4-(Octoxy)benzyl alcohol; .
[0012] 4'-Hydroxy-4-cyanobiphenyl.
[0013] It should be noted that the chemical properties of the patterning process match the graft bond types of the functionalized small molecules one-to-one: such as Figure 1 As shown: (a) Boronate bonds hydrolyze under liquid water or acidic conditions, where acid can accelerate hydrolysis and inhibit the re-bonding of small molecules with hydroxyl groups after removal. Therefore, boronate type orientation layers are locally treated with water, water vapor, acidic solutions or acidic atmospheres, preferably acidic solutions or acidic atmospheres; (b) Acetal bonds hydrolyze under acid catalysis but are stable under neutral and alkaline conditions. Therefore, acetal type orientation layers are locally treated with acidic solutions or acidic atmospheres; (c) Carbonate bonds hydrolyze under alkaline conditions. Therefore, carbonate type orientation layers are locally treated with alkaline solutions or alkaline atmospheres.
[0014] The aforementioned localized patterning process refers to the process of actively applying a sufficient amount of processing medium (at least one of the following methods: inkjet printing, spraying, dotting, mask fumigation, mask wetting, or local wiping; preferably, liquid media are applied by printing or wetting, and gaseous media by fumigation) to a predetermined area of the alignment layer after the alignment processes of the two alignment layers have been completed and before the liquid crystal cell is assembled, and maintaining the application for a certain period of time. If the processing medium does not match the bond type, the grafted functionalized small molecules cannot be selectively removed, and an effective hidden pattern cannot be formed.
[0015] Preferably, the transparent substrate is transparent glass or transparent resin.
[0016] Preferably, both alignment layers that make up the liquid crystal cell are patterned, and the patterns on the two alignment layers are aligned and overlap each other, so that the same pattern can be seen on both sides of the label when the pattern is displayed.
[0017] Preferably, the preset pattern is at least one of QR code, barcode, text, graphic, digital code, and identifier.
[0018] It should be further noted that after the liquid crystal filling and edge sealing are completed, the alignment layer of the anti-counterfeiting label is sandwiched between two substrates and sealed around the edges with edge sealing adhesive, only contacting the hydrophobic cholesteric liquid crystal. The sealed boundary formed by the edge sealing adhesive prevents external moisture from intruding, and the solubility of water in the hydrophobic liquid crystal layer is extremely low. It is difficult for external environmental humidity to reach the alignment layer and accumulate on its surface to form an effective amount of water that can cause hydrolysis. Therefore, it will not affect the preservation of the hidden pattern or the function of the label during storage and use.
[0019] Preferably, the cholesteric liquid crystal of the present invention is injected into the sandwich structure at a temperature above its clearing point. At this temperature, the liquid crystal is in an isotropic state with low viscosity, allowing it to quickly and uniformly fill the sandwich structure via capillary action; simultaneously, it ensures that the injection process itself does not introduce uncontrolled thermal history, allowing the label to cool from a uniform isotropic initial state to establish an initial hidden state. If injection is performed at a temperature below the clearing point, the liquid crystal viscosity is high, the injection is slow, and air bubbles are easily left behind. This results in uneven liquid crystal filling and inconsistent structural color within the sandwich structure, potentially affecting the normal hiding of the pattern.
[0020] Preferably, the polyvinyl alcohol is a partially or fully hydrolyzed polyvinyl alcohol, and the mass concentration of polyvinyl alcohol in the orientation layer coating solution is 0.1-10 wt%; and / or, the solvent used to prepare the orientation layer coating solution is at least one of a polar protic solvent and a polar aprotic solvent; and / or, in the orientation layer, the grafting rate of functionalized small molecules on polyvinyl alcohol is 0.01%-20%, and the grafting rate is defined as the ratio of the number of moles of functionalized small molecules grafted onto polyvinyl alcohol to the number of moles of polyvinyl alcohol repeating units.
[0021] Preferably, the coating method adopted by the orientation layer coating liquid includes at least one of spin coating, blade coating, drop coating, spray coating, dip coating, slot coating or inkjet printing, wherein the spin coating speed is 500 to 10000 rpm; and / or, the drying or annealing temperature is 20 to 100°C.
[0022] Preferably, the nematic liquid crystal is selected from at least one of 4-cyano-4'-pentylbiphenyl (5CB), 4-cyano-4'-n-heptylbiphenyl (7CB), 4-cyano-4'-octylbiphenyl (8CB), 4-cyano-4'-n-octyloxybiphenyl (8OCB), and 4''-pentyl-4-cyano-p-terphenyl (5CT); and / or, the chiral agent is selected from chiral agents with the same chiral induction effect, such as R5011, S811, R811, S1011, R1011, S5011, and CB15; and / or, the chiral agent content is 0.5 to 30 wt% of the total mass of the cholesteric phase liquid crystal. When the nematic liquid crystal is selected from multiple liquid crystal monomers, the preferred choice is a mixed liquid crystal E7, which is composed of 51 wt% 5CB, 25 wt% 7CB, 16 wt% 8OCB, and 8 wt% 5CT.
[0023] According to a second aspect of the present invention, the present invention also provides an anti-counterfeiting label prepared by the preparation method of the first aspect. The anti-counterfeiting label has a hidden pattern or low contrast under normal observation conditions, and only reveals a structural color pattern after undergoing a predetermined thermal history process.
[0024] According to a third aspect of the present invention, the present invention also provides a method for displaying a pattern on an anti-counterfeiting label according to the second aspect, wherein the anti-counterfeiting label displays a structural color pattern after undergoing a preset thermal history process; the preset thermal history process includes at least one cycle of the following heating / cooling process, specifically: heating from the low temperature region of the cholesteric liquid crystal to the cholesteric temperature region, heating to a temperature higher than the clearing point of the cholesteric liquid crystal, and cooling from the temperature higher than the clearing point to the cholesteric temperature region when the pattern is displayed.
[0025] According to a fourth aspect of the invention, the invention also provides the application of the anti-counterfeiting label of the second aspect in anti-counterfeiting marks, QR code anti-counterfeiting, information encryption, hidden patterns, temperature history records, structural color displays, decorative materials, or smart response devices.
[0026] Compared with the prior art, the present invention can achieve the following beneficial effects: This invention enables structural color patterning under ordinary laboratory conditions and can be applied commercially on a large scale. The pattern can be designed as a QR code, barcode, text, or graphic. The pattern display depends on a preset thermal history process, which has good concealment and recognizability. The preparation conditions are mild and the raw materials are readily available, making it suitable for scenarios such as anti-counterfeiting labels, information encryption, and temperature history recording.
[0027] The anti-counterfeiting label of this invention, because the hidden pattern is chemically fixed within the label, is not for single use: after the pattern appears, cooling the label to a low-temperature zone and then heating it back to the cholesteric phase temperature zone will cause the pattern to reappear. After undergoing another thermal history beyond the clearing point, the pattern will reappear, and the display and concealment can be cyclical. After multiple temperature cycles, the reflectance spectra of the treated and untreated areas remain basically consistent, indicating that the patterned information has good cyclic stability. Simultaneously, the sandwich encapsulation structure isolates the alignment layer carrying the pattern information from the external environment, making it difficult for external moisture to penetrate and reach the alignment layer. Therefore, the label is unaffected by environmental humidity and other factors during daily storage and use, exhibiting good environmental stability. Attached Figure Description
[0028] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0029] Figure 1 This is a schematic diagram illustrating the mechanism of the reaction between the functionalized small molecules of this invention and polyvinyl alcohol, as well as the hydrolysis and dehydration of the generated borate ester bonds, acetal bonds, and carbonate bonds.
[0030] Figure 2These are photographs of the anti-counterfeiting label obtained in Embodiment 1 of the present invention taken at various temperature points during a preset thermal history process.
[0031] Figure 3 The image shows the temperature-varying reflectance spectrum of the anti-counterfeiting label obtained in Embodiment 1 of the present invention at different temperature points during a complete thermal history cycle; where (a) is the temperature-varying reflectance spectrum of the patterned area (printed area), (b) is the temperature-varying reflectance spectrum of the unpatterned area (unprinted area), and the columns from bottom to top are the reflectance spectra of the 15°C heating stage, the 30°C heating stage, the 50°C heating stage, the 30°C cooling stage, and the 15°C cooling stage.
[0032] Figure 4 The image shows the cyclic reflectance spectrum of the anti-counterfeiting label obtained in Embodiment 1 of the present invention at a temperature of 30°C during 7 cycles of temperature increase and decrease; wherein, (a) is the reflectance spectrum of the patterned area (printed area) at a temperature of 30°C in each cycle, and (b) is the reflectance spectrum of the unpatterned area (unprinted area) at a temperature of 30°C in each cycle. The arrows in the figure indicate the direction of increasing cycle number.
[0033] Figure 5 These are photographs of the anti-counterfeiting label obtained in Comparative Example 1 of the present invention taken at various temperature points during a preset thermal history process.
[0034] Figure 6 These are photographs of the anti-counterfeiting label obtained in Comparative Example 2 of the present invention taken at various temperature points during a preset thermal history process.
[0035] Figure 7 These are photographs of the anti-counterfeiting label obtained in Comparative Example 3 of the present invention taken at various temperature points during a preset thermal history process.
[0036] Figure 8 These are photographs of the anti-counterfeiting label obtained in Comparative Example 4 of the present invention taken at various temperature points during a preset thermal history process.
[0037] Figure 9 These are photographs of the anti-counterfeiting label obtained in Embodiment 2 of the present invention taken at various temperature points during a preset thermal history process.
[0038] Figure 10 These are photographs of the anti-counterfeiting label obtained in Embodiment 3 of the present invention taken at various temperature points during a preset thermal history process.
[0039] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0040] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0041] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0042] Example 1: Structural color patterning method for borate ester type orientation layers This embodiment uses 4-(octoxy)phenylboronic acid as a functionalized small molecule to prepare a thermally history-programmable structural color patterned anti-counterfeiting label based on cholesteric liquid crystal (the hidden pattern is a "dragon" pattern). The specific method is carried out in the following steps: S1. Preparation of Orientation Layer S1-1. Weigh 0.100g of polyvinyl alcohol 1788 and 9.900g of deionized water, add them to a 20mL glass sample bottle, place the sample bottle in an 80℃ oil bath, and stir at 600rpm for 4h using a magnetic stir bar to obtain a polyvinyl alcohol aqueous solution with a mass fraction of 1.0wt%.
[0043] S1-2. Weigh 1.0 mg of 4-(octoxy)phenylboronic acid, add 1.0 mL of anhydrous ethanol and 0.2 mL of dimethyl sulfoxide, sonicate for 5 min to obtain a transparent or uniformly dispersed stock solution.
[0044] S1-3. Add all of the above stock solution to 10.0g of the obtained polyvinyl alcohol aqueous solution, and stir at 500rpm for 6h at 50℃ to obtain borate ester type orientation layer coating solution.
[0045] S1-4. A 2.5cm × 2.5cm ultra-clear glass slide was ultrasonically cleaned sequentially with detergent aqueous solution, deionized water, and ethanol for 10 min each. After drying with nitrogen, it was placed in a UV ozone cleaner for 15 min. 100 μL of the above-obtained coating solution was dropped onto the center of the glass slide, and the slide was spin-coated at 5000 rpm for 60 s. The spin-coated sample was then annealed sequentially at room temperature for 30 min, 40℃ for 10 min, 60℃ for 20 min, 80℃ for 60 min, 100℃ for 10 min, and 60℃ for 10 min to form a transparent and uniform orientation layer on the glass slide.
[0046] S2. Friction Orientation and Pattern Area Processing S2-1. Friction Orientation: The orientation layer is rubbed unidirectionally using liquid crystal friction cloth. The normal friction force is 5N, the friction speed is 50mm / s, and the number of rubs is 1.
[0047] S2-2. Patterning process: 0.01 mol / L hydrochloric acid aqueous solution is loaded into the micro-volume inkjet printer. The printhead temperature is set to 25℃ and the printing dot spacing is set to 80 μm. The pattern ("dragon" pattern) is printed on the rubbed surfaces of the two orientation layers to form a hidden pattern area containing the "dragon" pattern. The inkjet printer hot stage is set to 60℃.
[0048] S3. Assembly of the LCD cell S3-1. Using 10μm diameter silica microspheres as spacers, two glass plates that have been rubbed and printed with the same pattern are stacked and assembled into a liquid crystal cell by means that the rubbing orientation directions of their alignment layers are parallel to each other and opposite to each other, and the patterns of the two plates are aligned and overlapped. The printed patterns are all located in the inner layer of the liquid crystal cell and can directly contact the liquid crystal that is subsequently injected.
[0049] S3-2. The edges of the LCD cell are sealed with NOA61 UV-curable adhesive, cured by irradiation under 365nm UV light for 3 minutes, and a crystal filling port is reserved.
[0050] S4. Assembly of anti-counterfeiting labels S4-1. Preparation of cholesteric liquid crystal: Weigh 95 mg of 8CB (4-cyano-4'-octylbiphenyl) and 5 mg of R5011 chiral agent (chemical name: (13BR)-5,6-dihydro-5-(trans-4-propylcyclohexyl)-4H-dinaphtho[2,1-F:1',2'-H][1,5]dioxane-nonatetraene) and add them to a 2 mL centrifuge tube, then add 1.0 mL of chloroform. Place the centrifuge tube on a vortex mixer and mix for 2 min, then sonicate in an ultrasonic cleaner for 10 min, and then evaporate overnight on an 80℃ hot plate to obtain cholesteric liquid crystal.
[0051] S4-2. Place the liquid crystal cell and cholesteric liquid crystal on a 50°C hot stage (50°C is higher than the clearing point of this cholesteric liquid crystal, at which point the liquid crystal is in an isotropic state with low viscosity, which can be quickly and uniformly filled without introducing uncontrolled thermal history). Fill the cholesteric liquid crystal into the liquid crystal cell through capillary action and seal the filling port with NOA61 to obtain an anti-counterfeiting label with programmable structural color patterning based on the thermal history of cholesteric liquid crystal.
[0052] S5. The pattern on the anti-counterfeiting label is displayed. S5-1. Place the obtained anti-counterfeiting label on a temperature-controlled heating platform and heat it from 15℃ to 30℃ at a rate of 1℃ / min. Observe that the overall color is blue with a structural color. Continue to heat it to 50℃, where it is unstructured and maintain this state for 5 minutes. Then, cool it down to 30℃ at a rate of 1℃ / min. At this point, the unprinted area is unstructured and the printed area is blue with a structural color. The contrast between the two makes the preset "dragon" pattern appear.
[0053] S5-2. Repeat this step to make the pattern on the anti-counterfeiting label appear and disappear repeatedly.
[0054] Experimental Results and Analysis (1) Results of physical observation The anti-counterfeiting label obtained in Example 1 was placed on a temperature-controlled heating platform and its temperature was changed according to the program of 15℃→30℃→50℃→30℃→15℃→30℃. Photos of the actual product were taken at each temperature point. The results are as follows: Figure 2 As shown. During the initial heating phase, at 15℃, the entire label was in a whitish state without any structured color and no pattern was visible. When the temperature reached 30℃, the entire label exhibited a uniform blue structured color, with no indistinguishable difference between the printed and unprinted areas, and the "dragon" pattern was hidden. When the temperature continued to rise to 50℃ (beyond the clearing point), the structured color disappeared, and the label became unstructured. When the temperature was lowered from 50℃ to 30℃ at a rate of 1℃ / min, the printed area retained its blue structured color, while the unprinted area became unstructured, creating a clear contrast. The colorless "dragon" pattern was clearly visible against the blue background, with sharp and identifiable edges. When the temperature was lowered again to 15℃, the entire label again became unstructured, and the pattern was hidden. When the temperature was raised to 30℃ again, the label returned to a uniform blue color, and the pattern was hidden again. These results indicate that the pattern only appears after a preset thermal history of heating past the clearing point and cooling to the cholesteric phase temperature range (30℃), and the appearance and hiding can be repeatedly switched according to the thermal history.
[0055] (2) Variable temperature spectral characterization results The variable-temperature reflectance spectra of the patterned area (printed area) and the unpatterned area (unprinted area) were measured at various temperature points during the same thermal history cycle. The results are as follows: Figure 3 As shown, (a) is the temperature-varying reflectance spectrum of the patterned region, and (b) is the temperature-varying reflectance spectrum of the unpatterned region. The columns, from bottom to top, represent the reflectance spectra at heating stages of 15℃, 30℃, 50℃, 30℃, and 15℃. The vertical axis represents reflectance (any unit, au), and the horizontal axis represents wavelength (nm). Figure 3As can be seen, during the heating stage, both the patterned and unpatterned regions exhibit structural color reflection peaks at 30℃, with peak positions of approximately 504nm and 505nm respectively, corresponding to the blue structural color visible to the naked eye. At this point, the spectra of the two regions are similar, and the pattern is hidden. When the temperature is increased to 50℃ (beyond the clearing point), the reflection peaks of both regions disappear. When the temperature is reduced to 30℃, the patterned region reappears with a reflection peak at approximately 501nm, restoring its structural color, while the unpatterned region shows no obvious reflection peak during the 30℃ cooling stage, remaining in a state without structural color. Further cooling to 15℃ causes the reflection peaks of both regions to disappear. The difference in the reflection spectra of the patterned and unpatterned regions at the 30℃ cooling state corresponds one-to-one with the appearance of the "dragon" pattern in the aforementioned photograph, confirming from the spectrum that the pattern appearance originates from the contrast created by the patterned region retaining its structural color after cooling beyond the clearing point, while the unpatterned region loses its structural color.
[0056] (3) Cyclic stability (repeatable explicit and implicit verification) To examine the repeatability of the pattern's visibility, the anti-counterfeiting label obtained in Example 1 was tested at 15°C. The temperature was repeatedly increased and decreased at a rate of 1℃ / min, passing through 50℃ (including a 30℃ mark and a clearing point). Reflectance spectra of the patterned (printed) and unpatterned (unprinted) areas were collected only at each 30℃ mark. The 30℃ mark passed during the heating process was recorded as the 30℃ heating state, and the 30℃ mark passed during the cooling process was recorded as the 30℃ cooling state. The results are as follows: Figure 4As shown, (a) is the cyclic reflectance spectrum of the patterned region and (b) is the cyclic reflectance spectrum of the unpatterned region, with the arrows indicating the direction of increasing cycle number. It can be seen that in the seven consecutive heating and cooling cycles collected, the patterned region consistently exhibited a distinct structural color reflectance peak at the 30℃ cooling state, with the peak position remaining stable around approximately 500 nm in each cycle. The peak intensity did not show significant attenuation, and the peak shape was basically consistent. In contrast, the unpatterned region showed no distinct reflectance peak and remained unpatterned in each cycle at the 30℃ cooling state. On the other hand, at the 30℃ heating state (without exceeding the clearing point), both the patterned and unpatterned regions consistently maintained a distinct structural color reflectance peak, with the peak position also remaining stable around approximately 500 nm in each cycle and the peak shape being basically consistent. This indicates that the state of both regions exhibiting structural color and hidden patterns can be stably repeated without experiencing a thermal history exceeding the clearing point. Furthermore, after subjecting the anti-counterfeiting label to 50 consecutive heating and cooling cycles, physical observation showed no significant attenuation in the display and hiding behavior of the pattern or the display contrast. These results indicate that after multiple thermal history cycles, both the patterned and unpatterned areas exhibit structural color (pattern hidden) at a 30°C heating state, and a stable difference of "with structured color / without structured color" (pattern displayed) at a 30°C cooling state. This difference in display did not show significant attenuation. The anti-counterfeiting label of this invention is not for single use; the pattern can be repeatedly displayed and hidden according to a preset thermal history, exhibiting good cycle stability and reusability.
[0057] Based on the above physical observations and temperature-varying spectra ( Figure 3 ) and cyclic spectrum ( Figure 4 As a result, the anti-counterfeiting label obtained in Example 1 achieved the following: the pattern is normally hidden, triggered by a preset thermal history (heating past the clearing point and then cooling down to the cholesteric phase temperature zone), and the pattern can be repeatedly switched between being hidden and being displayed. The pattern is characterized by the contrast between the unprinted area being unstructured and the printed area maintaining its structured color after cooling past the clearing point. The label also maintains good stability after being verified by up to 50 heating and cooling cycles.
[0058] Comparative Example 1: Unpatterned Control Experiment The anti-counterfeiting label was prepared according to the same steps and parameters as in Example 1, except for step S4-2, which did not involve inkjet printing with hydrochloric acid solution (no patterning process). The remaining steps (including orientation layer preparation, assembly and injection, and thermal history procedure) were the same as in Example 1.
[0059] Test results: The sample obtained in Comparative Example 1 exhibited a uniform structural color throughout the heating phase (before passing the clearing point); after passing the clearing point and cooling to 30℃, the entire sample transformed into a non-structural color state. Throughout the entire thermal history, the sample remained uniform and did not display any patterns. Figure 5As shown. This indicates that when there is only a functionalized orientation layer without local patterning, the entire film simultaneously enters an unstructured color state after passing the clearing point and cooling down, and cannot form a pattern.
[0060] Comparative Example 2: Blank Control Experiment Without Functionalized Small Molecules The anti-counterfeiting label was prepared according to the same steps and parameters as in Example 1, except that 4-(octoxy)phenylboronic acid was not added in steps S1-2, i.e. the orientation layer was a pure polyvinyl alcohol orientation layer. The remaining steps (including inkjet printing of hydrochloric acid solution and thermal history program) were the same as in Example 1.
[0061] Test Results: After undergoing a thermal history of heating past the clearing point and cooling to 30°C, the sample obtained in Comparative Example 2 still exhibited uniform structural color throughout. No contrast between the printed and unprinted areas was formed, and no pattern was displayed. Figure 6 As shown. This indicates that the pure polyvinyl alcohol orientation layer does not contain functionalized small molecules, does not respond to the local patterning treatment, and cannot allow any region to enter an unstructured color state after passing the clearing point and cooling.
[0062] Comparative Example 3: Control experiment where the liquid crystal compatibility end of functionalized small molecules does not meet the requirements The anti-counterfeiting label was prepared according to the same steps and parameters as in Example 1, except that 4-(octyloxy)phenylboronic acid was replaced with an equimolar amount of 2-thiopheneboronic acid. All other steps were the same as in Example 1.
[0063] The structural formula of 2-thiopheneboronic acid is: It can be seen that it has a reaction end (-B(OH)2) that can form a borate bond with the hydroxyl group of polyvinyl alcohol, so its film formation, grafting and removal behavior under the action of hydrochloric acid printing solution are comparable to those of Example 1; however, its other end is a thiophene five-membered heterocycle, which does not belong to the liquid crystal compatible end group described in this invention.
[0064] Test Results: After undergoing a thermal history of heating past the clearing point and cooling to 30°C, the sample obtained in Comparative Example 3 still exhibited a uniform structural color, consistent with the blank control (Comparative Example 2) without functionalized small molecules. No contrast between the printed and unprinted areas was formed, and no pattern could be displayed. Figure 7As shown. This is because the thiophene end has poor compatibility with the rod-shaped cyanobiphenyl liquid crystal, preventing the area from entering a structureless color state after cooling past the clearing point. Therefore, the unprinted area retains its structured color after cooling, resulting in no contrast with the printed area. Since this control only changed the compatibility end of the functionalized small molecule while retaining the same reaction end as in Example 1, the inability to form a pattern can be solely attributed to the failure of the compatibility end to meet the requirements. This fully demonstrates that the liquid crystal compatibility end of the functionalized small molecule is a necessary structure for the untreated area to exhibit a structureless color after a preset thermal history, thereby creating a pattern contrast with the treated area.
[0065] To further demonstrate the beneficial effects of the present invention, the same preparation method as in Example 1 was used, except that the liquid crystal compatible end groups of the functionalized small molecule 4-(octoxy)phenylboronic acid were replaced. Specifically, 4-(octoxy)phenylboronic acid was replaced with 4-(hexyloxy)phenylboronic acid or -4'-cyanobiphenyl-4-boronic acid. Physical observation showed that the pattern display / hiding behavior of the final anti-counterfeiting label was basically consistent with that of Example 1: before passing the clearing point, the entire label had structural color and the pattern was hidden; after experiencing the thermal history of passing the clearing point, the printed area showed color, while the unprinted area had no structural color, and the pattern was clearly visible; when cooled to 15°C, there was no structural color and the pattern was hidden; when heated again to 30°C, the label returned to a uniform blue color and the pattern was hidden, indicating that the functionalized small molecule of the present invention, by replacing different liquid crystal compatible end groups, can also achieve the thermal history programmable structural color patterning effect of the present invention.
[0066] Comparative Example 4: Control experiment on localized treatment solutions with mismatched chemical bond types The anti-counterfeiting label was prepared according to the same steps and parameters as in Example 1, except that in step S2-2, the 0.01 mol / L hydrochloric acid aqueous solution was replaced with a 0.01 mol / L sodium hydroxide aqueous solution. All other steps were the same as in Example 1.
[0067] The borate ester bonds of the functionalized small molecule 4-(octoxy)phenylboronic acid are not hydrolyzed under alkaline conditions, and the bond type of the alkaline printing solution does not match that of the borate ester type orientation layer.
[0068] Test Results: After undergoing a thermal history of heating past the clearing point and cooling to 30°C, the sample obtained in Comparative Example 4 exhibited unstructured color in both the printed and unprinted areas, with no structural color contrast between the two areas, and the pattern was not visible. Figure 8 As shown. This is because the alkaline printing solution cannot hydrolyze borate ester bonds, and the functionalized small molecules in the printed area are not removed. Like the unprinted area, they retain the characteristic of entering an unstructured color state after passing the clearing point and cooling, thus failing to form a pattern. This fully demonstrates that the matching relationship between the local patterning processing medium and the graft bond type of the functionalized small molecules is the key to achieving patterning in this invention.
[0069] Example 2: Method for patterning structural color of acetal-type alignment layer In this example, 4-(octyloxy)benzaldehyde is used as the functional small molecule to prepare a thermal history programmable structural color patterned anti-counterfeiting label (the hidden pattern is the Chinese character "马" (horse)). This method is carried out according to the following steps: S1. Preparation of alignment layer S1-1. Weigh 0.100g of polyvinyl alcohol 1788 and 8.000g of deionized water, and stir at 80°C at 600rpm for 4h; cool the system to 60°C, add 2.000g of dimethyl sulfoxide, and continue stirring for 30min to obtain a polyvinyl alcohol water / dimethyl sulfoxide mixed solution.
[0070] S1-2. Weigh 1.0mg of 4-(octyloxy)benzaldehyde and 5.0mg of p-toluenesulfonic acid, add 0.5mL of dimethyl sulfoxide, and perform ultrasonication for 5min to obtain a functional small molecule solution.
[0071] S1-3. Add all the above functional small molecule solution into the above polyvinyl alcohol water / dimethyl sulfoxide mixed solution, stir at 65°C at 500rpm for 8h. After the reaction is completed, add 5μL of triethylamine and stir for 5min to make the system nearly neutral, so as to obtain the acetal-type alignment layer coating solution.
[0072] S1-4. Take 100μL of the obtained coating solution and drop it onto a 2.5cm×2.5cm ultra-white glass slide that has been treated with ultraviolet ozone for 15min, and spin-coat it on a spin coater at 5000rpm for 60s. After spin-coating, the sample is sequentially placed at room temperature for 30min, kept at 40°C for 10min, kept at 60°C for 30min, kept at 80°C for 60min, kept at 100°C for 10min, and annealed at 60°C for 10min to obtain a glass substrate with an alignment layer.
[0073] S2. Rubbing alignment and pattern region treatment S2-1. Rubbing alignment: A liquid crystal rubbing cloth is used to perform unidirectional rubbing on the alignment layer, the normal force of rubbing is 5N, the rubbing speed is 50mm / s, and the number of rubbing times is 1.
[0074] S2-2. Patterning treatment: A 0.01mol / L hydrochloric acid ethanol / water mixed solution (with a volume ratio of ethanol to water of 1:1) is filled into a micro inkjet printing device, the nozzle temperature is set to 25°C, the printing dot pitch is 80μm, and pattern printing is performed on the rubbed surfaces of the two alignment layers respectively according to the preset pattern (the Chinese character "马" (horse) pattern) to form a hidden pattern region containing the "马" pattern, and the hot stage of the inkjet printer is set at 60°C.
[0075] S3. Assembly of liquid crystal cell S3-1. Using silica microspheres with a diameter of 10μm to define the thickness, two glass plates that have been rubbed and printed with the same pattern are stacked and assembled into a liquid crystal cell in a manner where the rubbing directions are parallel and opposite to each other and the patterns on the two plates are aligned and overlapped. The printed patterns are all located in the inner layer of the liquid crystal cell and can directly contact the liquid crystal that is subsequently injected.
[0076] S3-2. The edges of the LCD cell are sealed with NOA61 UV-curable adhesive, cured by irradiation under 365nm UV light for 3 minutes, and a crystal filling port is reserved.
[0077] S4. Assembly of anti-counterfeiting labels S4-1. Preparation of cholesteric liquid crystal: Weigh 95 mg of 8CB (4-cyano-4'-octylbiphenyl) and 5 mg of R5011 chiral agent and add them to a 2 mL centrifuge tube, then add 1.0 mL of chloroform. Place the centrifuge tube on a vortex mixer and mix for 2 min, then sonicate in an ultrasonic cleaner for 10 min, and finally evaporate overnight on an 80°C hot plate to obtain the cholesteric liquid crystal.
[0078] S4-2. Place the liquid crystal cell and cholesteric liquid crystal on a 60°C hot stage (above the clearing point of the cholesteric liquid crystal, at which point the liquid crystal is in an isotropic state with low viscosity, which can be quickly and uniformly filled without introducing uncontrolled thermal history). Fill the cholesteric liquid crystal into the liquid crystal cell through capillary action and seal the filling port with NOA61 to obtain an anti-counterfeiting label with programmable structural color patterning based on the thermal history of the cholesteric liquid crystal.
[0079] S5. The pattern on the anti-counterfeiting label is displayed. The obtained anti-counterfeiting label is placed on a temperature-controlled heating platform. When the temperature is raised from 15℃ to 30℃ (without exceeding the clearing point), the entire label shows a uniform structural color and the pattern is hidden. When the temperature is raised to 50℃ and held for 5 minutes, and then lowered to 30℃, the printed area maintains the blue structural color, the unprinted area turns into an unstructured color, and the preset "horse" pattern appears.
[0080] Physical observation revealed that the pattern display behavior of the acetal-type label was basically consistent with that of Example 1: before passing the clearing point, the entire label had structural color and the pattern was hidden; after passing the clearing point, the printed area showed color, while the unprinted area had no structural color, and the pattern was clearly visible; when cooled to 15°C, the pattern was hidden again; when heated to 30°C again, the label returned to a uniform blue color and the pattern was hidden. Figure 9 The demonstration shows that the acetal-type functionalized small molecules of the present invention can also achieve the thermal history programmable structural color patterning effect of the present invention.
[0081] Example 3: Structural Color Patterning Method for Carbonate-Type Orientation Layers In this example, 4-(octyloxy)benzyl alcohol is used as the functional small molecule to prepare a thermal history programmable structural color patterned anti-counterfeiting label (the hidden pattern is the Chinese character "horse"). This method is carried out according to the following steps: S1. Preparation of alignment layer S1-1. Weigh 0.100 g of polyvinyl alcohol 1788 and add it to 10.0 mL of anhydrous dimethyl sulfoxide, stir at 80°C at 600 rpm for 4 h to obtain a polyvinyl alcohol dimethyl sulfoxide solution, and cool the polyvinyl alcohol dimethyl sulfoxide solution to 60°C for later use.
[0082] S1-2. Weigh 1.0 mg of 4-(octyloxy)benzyl alcohol and 1.0 mg of carbonyldiimidazole and place them in a reaction flask; add 1.0 mL of anhydrous dimethyl sulfoxide, and stir at 40°C for 2 h to obtain a functional small molecule solution.
[0083] S1-3. Add all the above functional small molecule solution into the polyvinyl alcohol dimethyl sulfoxide solution, then add 1.0 mg of 4-dimethylaminopyridine and 20 μL of triethylamine, stir at 60°C at 500 rpm for 8 h to obtain a carbonate-type alignment layer coating solution.
[0084] S1-4. Clean a 2.5 cm × 2.5 cm ITO glass slide sequentially with detergent aqueous solution, deionized water, and ethanol by ultrasonication for 10 min each, blow dry with nitrogen, and then treat it in an ultraviolet ozone cleaner for 15 min. Take 100 μL of the coating solution obtained above and drop it on the center of the glass slide, then spin-coat it on a spin coater at 5000 rpm for 60 s. After spin-coating, the sample is sequentially left at room temperature for 30 min, kept at 40°C for 10 min, kept at 60°C for 30 min, kept at 80°C for 60 min, kept at 100°C for 10 min, and annealed at 60°C for 10 min to obtain a glass substrate with an alignment layer.
[0085] S2. Rubbing alignment and pattern area treatment S2-1. Rubbing alignment: A liquid crystal rubbing cloth is used to perform unidirectional rubbing on the alignment layer, the rubbing normal force is 5 N, the rubbing speed is 50 mm / s, and the number of rubbing times is 1.
[0086] S2-2. Patterning treatment: A 0.01 mol / L sodium hydroxide ethanol / water mixed solution is filled into a micro inkjet printing device, wherein the volume ratio of ethanol to water is 1:1, the nozzle temperature is set to 25°C, the printing dot pitch is set to 80 μm, and pattern printing is performed on the rubbed surfaces of the two alignment layers respectively according to a preset pattern (the Chinese character "horse" pattern) to form a hidden pattern area containing the "horse" pattern, and the hot stage of the inkjet printer is set to 60°C.
[0087] S3. Assembly of liquid crystal cell S3-1. Using 10μm diameter silica microspheres as spacers, two glass plates that have been rubbed and printed with the same pattern are stacked and assembled into a liquid crystal cell in a manner where the rubbing directions are parallel and opposite to each other and the patterns on the two plates are aligned and overlapped. The printed patterns are located in the inner layer of the liquid crystal cell and can directly contact the liquid crystal that is subsequently injected.
[0088] S3-2. The edges of the LCD cell are sealed with NOA61 UV-curable adhesive, cured by irradiation under 365nm UV light for 3 minutes, and a crystal filling port is reserved.
[0089] S4. Assembly of anti-counterfeiting labels S4-1. Preparation of cholesteric liquid crystal: Weigh 95 mg of 8CB (4-cyano-4'-octylbiphenyl) and 5 mg of R5011 chiral agent and add them to a 2 mL centrifuge tube, then add 1.0 mL of chloroform. Place the centrifuge tube on a vortex mixer and mix for 2 min, then sonicate in an ultrasonic cleaner for 10 min, and finally evaporate overnight on an 80°C hot plate to obtain the cholesteric liquid crystal.
[0090] S4-2. Place the liquid crystal cell and cholesteric liquid crystal on a 60°C hot stage (above the clearing point of the cholesteric liquid crystal, at which point the liquid crystal is in an isotropic state with low viscosity, which can be quickly and uniformly filled without introducing uncontrolled thermal history). Fill the cholesteric liquid crystal into the liquid crystal cell through capillary action and seal the filling port with NOA61 to obtain an anti-counterfeiting label with programmable structural color patterning based on the thermal history of the cholesteric liquid crystal.
[0091] S5. The pattern on the anti-counterfeiting label is displayed. The obtained anti-counterfeiting label is placed on a temperature-controlled heating platform. During the temperature rise and fall process before the clearing point is reached, the entire label is in structural color and the preset pattern is hidden. After being heated to 50℃ and held for 5 minutes, and then cooled to 30℃, the printed area retains the blue structural color, the unprinted area turns into an unstructured color, and the preset "horse" pattern appears.
[0092] Physical observation revealed that the pattern display behavior of the carbonate-type label was consistent with that of Example 1: before passing the clearing point, the entire area had structural color and the pattern was hidden; after experiencing the thermal history of passing the clearing point, the printed area became colored, while the unprinted area had no structural color and the pattern was clearly displayed. Furthermore, it could be repeatedly hidden after low-temperature reset, as shown in the example. Figure 10 The demonstration shows that carbonate-type functionalized small molecules can also achieve the thermal history programmable structural color patterning effect of the present invention.
[0093] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.
Claims
1. A method for preparing a thermal history programmable structural color patterned anti-counterfeiting label, characterized in that, Includes the following steps: S1. Prepare an orientation layer coating solution containing polyvinyl alcohol and functionalized small molecules, coat it onto a transparent substrate to form a film, and dry or anneal it to obtain a substrate with an orientation layer. The functionalized small molecule is selected from one of the structures shown in formula (Ⅰ), (Ⅱ), and (Ⅲ): Wherein, R is a liquid crystal compatibility end composed of at least one of C1-C20 alkyl, C1-C20 alkoxy, phenyl, naphthyl, biphenyl, cyanophenyl, and cyanobiphenyl. When the functionalized small molecule is selected from the structure of formula (II), p-toluenesulfonic acid is also added to the orientation layer coating solution; When the functionalized small molecule is selected from the structure of formula (III), at least one of triethylamine, 4-dimethylaminopyridine and carbonyl diimidazole are also added to the orientation layer coating solution; S2. The alignment layer is surface-oriented using a friction method or equivalent friction method; then, a local patterning process is performed on the surface after the alignment process to form a hidden pattern area containing a preset pattern on the alignment layer. The chemical properties of the patterning process and the functionalized small molecules satisfy the following relationship: When the functionalized small molecule is selected from the structure of formula (I), the processing medium used for patterning is selected from at least one of water, water vapor, acidic solution or acidic atmosphere; When the functionalized small molecule is selected from the structure of formula (II), the processing medium used for patterning is selected from at least one of acidic solution or acidic atmosphere; When the functionalized small molecule is selected from the structure of formula (III), the processing medium used for patterning is selected from at least one of alkaline solution or alkaline atmosphere; S3. Take two patterned substrates with alignment layers and assemble them into a liquid crystal cell with their orientation directions parallel and opposite, and place the alignment layer inside the liquid crystal cell. S4. Cholesteric liquid crystal, including nematic liquid crystal and chiral agent, is poured into a liquid crystal cell and cured to obtain an anti-counterfeiting label based on the thermal history programmable structural color pattern of cholesteric liquid crystal.
2. The preparation method according to claim 1, characterized in that, The polyvinyl alcohol is a partially or fully hydrolyzed polyvinyl alcohol, and the mass concentration of polyvinyl alcohol in the orientation layer coating solution is 0.1 to 10 wt%; and / or, the solvent used to prepare the orientation layer coating solution is at least one of a polar protic solvent and a polar aprotic solvent; and / or, in the orientation layer, the grafting rate of functionalized small molecules on polyvinyl alcohol is 0.01% to 20%.
3. The preparation method according to claim 1, characterized in that, The coating method includes at least one of spin coating, blade coating, drop coating, spray coating, dip coating, slot coating or inkjet printing, wherein the spin coating speed is 500 to 10000 rpm; and / or the drying or annealing temperature is 20 to 100°C.
4. The preparation method according to claim 1, characterized in that, The patterning process employs at least one of the following methods: inkjet printing, spraying, dotting, mask fumigation, mask impregnation, or local wiping.
5. The preparation method according to claim 1, characterized in that, The nematic liquid crystal is selected from at least one of 4-cyano-4'-pentylbiphenyl, 4-cyano-4'-n-heptylbiphenyl, 4-cyano-4'-octylbiphenyl, 4-cyano-4'-n-octoxybiphenyl, and 4''-pentyl-4-cyano-p-terphenyl; and / or, the chiral agent is selected from at least one of R5011, S811, R811, S1011, R1011, S5011, and CB15; and / or, the chiral agent content is 0.5 to 30 wt% of the total mass of the cholesteric phase liquid crystal.
6. The preparation method according to claim 1, characterized in that, Both alignment layers that make up the liquid crystal cell are patterned, and the patterns on the two alignment layers are aligned and overlap each other.
7. The preparation method according to claim 1, characterized in that, The preset pattern is at least one of the following: QR code, barcode, text, graphic, digital code, and identifier.
8. An anti-counterfeiting label, characterized in that, The anti-counterfeiting label is prepared by any one of claims 1-7, and after undergoing a preset thermal history process, a structural color pattern is displayed; the preset thermal history process includes heating to a temperature higher than the cholesteric phase liquid crystal clearing point and then cooling down from the temperature higher than the clearing point to the cholesteric phase temperature range.
9. The method for displaying the pattern of an anti-counterfeiting label as described in claim 8, characterized in that, The anti-counterfeiting label displays a structural color pattern after undergoing a preset thermal history process; the preset thermal history process includes heating to a temperature higher than the cholesteric phase liquid crystal clearing point and then cooling down from the higher clearing point to the cholesteric phase temperature range.
10. The application of the anti-counterfeiting label as described in claim 8 in anti-counterfeiting marks, QR code anti-counterfeiting, information encryption, hidden patterns, temperature history records, structural color display, decorative materials, or smart response devices.
Citation Information
Patent Citations
Anti-counterfeit label capable of hiding pattern information, manufacturing method of anti-counterfeit label and pattern showing method of anti-counterfeit label
CN118219689A
Carbon nanomaterial with photochromism and water stimulation response as well as preparation method and application of carbon nanomaterial
CN119875274A